The Influence of Principal Leadership Style, Organizational Citizenship Behavior and Reards on Teacher Performance at Senior High School in Banda Aceh District - Said Ashlan; Irsan; Benyamin (International Journal of Science, Technology & Management, 2021)
This study aims to look at: (1) the effect of organizational citizenship behavior on teacher performance, and (2) the imbalance effect on teacher performance, (3) finding the teacher performance model the influence of organizational citizenship behavior and mismatches on teacher performance. The research subjects were teachers of public high schools in Banda Aceh with a total sample of 240 people who were taken by proportional stratified random sampling, the data were analyzed using path analysis after continuing to monitor all the research variables in the form of a matrix. The findings were obtained from the performance of public high school teachers in Banda Aceh City directly by the behavior of organizational citizens, and the imbalance. Based on testing the hypothesis it can be rejected: (1) there is a direct influence on the behavior of organizational citizens on teacher performance, and (2) there is a direct effect of imbalance on teacher performance. The results of the study provide an illustration that the relative direct influence of organizational citizenship behavior (X1) on teacher performance (X3), namely: ?31 = 0.233, and the relative direct influence of imbalance (X2) on teacher performance (X3), namely: ?32 = 0.055.